Effects of Different Types of Manure Application on Rice Yield and Improving Soil Effect - Ding Shengli; Tu Xiaofei; Wei Jing (E3S Web of Conferences, 2025)
In order to explore the effects of different kinds and different amounts of manure on rice growth and soil fertility, pot experiments were carried out on the basis of applying chemical fertilizer with equal nitrogen, and the optimum amount of manure was studied by systematically analyzing therice yield, SPAD of rice leaves, the dynamic change of inorganic nitrogen concentration in paddy field surface water and the physical and chemical properties of soil after rice harvest. The results showed that, on the basis of applying 192.8 kg·hm-2 urea (calculated as pure nitrogen), it was the best to increase the application of pig manure by one time (equivalent to 153.4 kg·hm-2) and chicken manure by one and a half times (equivalent to 203.1 kg·hm-2). At this time, the rice grain yield, straw yield, grain nitrogen uptake and straw were the best. Appropriate application of manure can effectively reduce the loss of nitrogen in field water, in which the application of pig manure can reduce ammonium nitrogen and nitrate nitrogen by 21.55% and 50.60% respectively, and the application of chicken manure can reduce ammonium nitrogen and nitrate nitrogen by 13.48% and 8.33% respectively. In addition, the application of manure increased the contents of total nitrogen, organic matter, available phosphorus and alkali-hydrolyzable nitrogen in the soil, which significantly improved the soil texture and soil fertility. In a word, applying 1 time of pig manure or 1.5 times of chicken manure on the basis of applying the same amount of chemical fertilizer can maximize rice yield and improve soil quality, while reducing the risk of nitrogen loss and environmental pollution. The research results can not only provide data reference for the selection of manure types and the ratio of organic and inorganic fertilizers in rice production, but also reduce the risk of environmental damage caused by fertilization.